Research Progress on Aptamer Electrochemical Biosensors Based on Signal Amplification Strategy - Jiangrong Yang; Yan Zhang (Sensors, 2025)
Aptamers have high specificity and affinity to target analytes, along with good stability and low cost, making them widely used in the detection of target substances, especially in the increasingly popular aptamer-based electrochemical biosensors. Aptamer-based electrochemical biosensors are composed of aptamers as the biorecognition elements and sensors that convert the biological interactions into electrical signals for the quantitative detection of targets. To detect low-abundance target substances, the improvement of the sensitivity of biosensors is a pursuit of researchers. Therefore, different amplification strategies for significantly enhancing the detection sensitivity of biosensors have been explored. Thus, this paper reviews the different amplification strategies with various functional materials to amplify the detection signals. Currently, such strategies commonly use gold nanoparticles to construct electrodes that facilitate the transfer of biological reactions or to obtain enhanced signals through nucleic acid amplification. Some strategies use nucleases for target recycling to further enhance the signals. This review discusses the recent progress in signal amplification methods and their applications, and proposes future directions of study to guide subsequent researchers in overcoming the limitations of previous approaches and to produce reproducible biosensors for clinical applications.